The effects of isomaltulose ingestion on gastric parameters and cycling performance in young men - Masashi Miyashita; Yuka Hamada; Kyoko Fujihira; Saki Namura; Miki Sakazaki; Kiyoaki Miyasaka; Yukie Nagai (Elsevier, 2019)
Background/Objective: Isomaltulose is a disaccharide with a low glycaemic index and plays a role in maintaining postprandial glucose. The maintenance of glucose availability during prolonged exercise has been shown to enhance exercise performance. The present study compared the effects of pre-exercise isomaltulose versus maltodextrin ingestion on gastric parameters and cycling performance in young men. Methods: Fourteen young men (mean ± S.D., age 23 ± 2 years) performed 60 min of continuous cycling at 75% of maximum heart rate followed by a 15-min exercise performance test while ingesting a 500-mL of water containing 100 mg of 13C-sodium acetate with either 50 g of isomaltulose or 50 g of maltodextrin. Gastrointestinal discomfort was assessed periodically using an 11-point visual analogue scale throughout the study. The gastric emptying rate was evaluated periodically with the 13C-sodium acetate breath test. For the exercise performance test, participants were instructed to pedal a cycle ergometer, exerting as much effort as possible at a self-selected pace. Results: Plasma glucose and insulin concentrations measured at 30 min after ingestion were lower in the isomaltulose trial than in the maltodextrin trial. There were no differences in mean power output during the exercise performance test, gastric emptying rate or the subjective feelings of gastrointestinal discomfort between both trials. Conclusion: Under the current exercise protocol, pre-exercise ingestion of isomaltulose compared with maltodextrin provided no additional benefit relative to gastric emptying or aerobic exercise performance. Both isomaltulose and maltodextrin ingestion did not influence gastrointestinal distress during 60 min of cycling and performance test. Keywords: Exercise performance, Gastrointestinal discomfort, Isomaltulose, Metabolic response, Stable isotope